Effects of soil- and foliar-applied silicon on the resistance of grapevine plants to freezing stress - Habibi, Ghader (Acta Biologica Szegediensis, 2015)
Grapes are frequently injured by freezing stress. Silicon (Si) is reported to reduce the effects of freezing on various crops. The main objective of this study was to elucidate the role of foliar- and soil-applied Si in enhancing grape (Vitis vinifera L.) tolerance to cold stress. The results indicated that the freezing stress dramatically decreased leaf fresh mass, relative water content, and caused an increased necrotic leaf area, but these effects were alleviated by both soil and foliar-applied Si. Foliar-applied Si reduced significantly damaging effects of freezing stress on maximum quantum yield of PSII after 2 and 96 h recovery after freezing treatment, while soil application of Si could not. This may be attributed to the enhancement of non-photochemical quenching, because of its effect on elevation of protective pigments; carotenoids, and more protection of PSII from photodamage following a foliar spray of Si. In addition, freezing stress increased membrane damage, as estimated by malondialdehyde content, while foliar Si application significantly decreased the membrane damage, because of an efficient scavenging by peroxidase, but soil application of Si could not. We conclude that foliar-applied Si can effectively alleviate adverse effects of freezing via maintenance of membrane integrity and alleviating photoinhibition during recovery.